Drug-endobiotic interaction effect of UGT enzymes inhibition on systemic bile acids levels in rat - TV Radhakrishna Mullapudi, Punna Rao Ravi (Journal of Applied Pharmaceutical Science, 2025)
Drug-endobiotic interactions (DEIs) arise when xenobiotics affect the biosynthesis, metabolism, and transportation of endobiotics, which alter endobiotics homeostasis. Their clinical significance depends on the role of specific endobiotics in health and disease conditions. Bilirubin and bile acids are crucial endobiotics primarily metabolized by UGT1A1 and UGT1A3 enzymes. Inhibition of these enzymes by xenobiotic drugs may result in DEIs, and the current study aims to investigate this research question. Zafirlukast was identified as a pan-inhibitor for UGT1A1 and UGT1A3 isoforms, while its inhibitory potential was verified using ezetimibe, a common substrate for UGT1A1/UGT1A3. Further, serum bilirubin and plasma bile acids were compared after 7 days of exposure to Zafirlukast with vehicle control. Serum bilirubin concentrations were not altered, while the concentrations of chenodeoxycholic acid and cholic acid reduced significantly, and deoxycholic acid, glycodeoxycholic acid, taurodeoxycholic acid, and tauro-α/β-muricholic acid levels remained unaffected. These changes in bile acid levels may be attributed to the biosynthetic feedback or metabolic feedforward mechanisms. These results reveal that inhibition of UGT1A1/UGT1A3 enzymes by xenobiotics may potentially alter the homeostasis of bile acids and may result in clinically significant DEIs.
Keywords: Xenobiotics, bile acids, UGT1A1, UGT1A3, Drug-endobiotic interactions